2021
DOI: 10.1186/s12889-021-11050-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the trend of AIDS incidence in Zhejiang, China based on the age-period-cohort model (2004–2018)

Abstract: Objective To predict the trend of AIDS in specific age groups and to determine the objective population for AIDS screening, this study explored the three transmission routes and characterized each patient group using the APC model based on the whole, local, and immigrant populations in Zhejiang, China. Methods The data recruited in this paper was obtained from the national Comprehensive AIDS Prevention and Control Information System - Antiviral The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
2
7
0
1
Order By: Relevance
“…Although there seems a growing number of HIV incidences, the overall growth rate in Hunan province has slowed down in recent years, implying the effectiveness of HIV prevention and control strategies. Most HIV infections in Hunan province are diagnosed in male patients, in agreement with other studies conducted from other provinces in China ( 27 , 31 ). Our study finds that the majority of HIV infections in Hunan province are elderly patients aged ≥50 years, which is agreement with other national surveys ( 32 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although there seems a growing number of HIV incidences, the overall growth rate in Hunan province has slowed down in recent years, implying the effectiveness of HIV prevention and control strategies. Most HIV infections in Hunan province are diagnosed in male patients, in agreement with other studies conducted from other provinces in China ( 27 , 31 ). Our study finds that the majority of HIV infections in Hunan province are elderly patients aged ≥50 years, which is agreement with other national surveys ( 32 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…A previous study ( 47 ) using data from the National Comprehensive AIDS Prevention and Control Information System in Zhejiang province indicated that the higher AIDS incidence risks were distributed in young people. It was consistent with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there seems a growing number of HIV incidences, the overall growth rate in Hunan province has slowed down in recent years, implying the effectiveness of HIV prevention and control strategies. Most HIV infections in Hunan province are diagnosed in male patients, in agreement with other studies conducted from other provinces in China (27,31). Our study finds that the majority of HIV infections in Hunan province are elderly patients aged ≥50 years, which is agreement with other national surveys (32)(33)(34).…”
Section: Discussionsupporting
confidence: 92%
“…Based on a large-scale cohort of 34,297 HIV-infected patients, our study presents the first survey of HIV infections (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) in Hunan province. Compared with other provinces in China, the HIV epidemic in Hunan province is not considered severe (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation